Interaction of epirubicin HCl with surfactants: Effect of NaCl and glucose - ÇAKIR, NEŞE; GÖKTÜRK, SİNEM (JOHN WILEY & SONS INC, 2004)
The interaction of an antitumoural drug, Epirubicin HCl, with anionic (sodiumdodecylsulfate; SDS), cationic (cetyltrimethylammonium bromide; CTAB), and nonionic (t-octylphenoxypolyethoxyethanol; TX-100, polyoxyethylenesorbitanmonolaurate; Tween 20) surfactants has been studied by absorption spectra as a function of surfactant concentration ranging from the premicellar to postmicellar region. At the concentrations below the critical micelle concentration (CMC), the equilibrium complex formation constant between Epirubicin cations and SDS anions has been determined by Job's method. Above the CMC, binding constant (K-b) of Epirubicin to various types of micelles has been calculated by means of the Benesi-Hildebrand Equation. The nonionic surfactant micelles showed stronger interaction than the ionic SDS micelles, and the binding tendency of Epirubicin followed the order: Tween 20 > TX-100 > SDS. Binding of Epirubicin also has been studied in the presence of NaCl and glucose because it is administered to patients intravenously in 0.9% NaCl or 5% glucose solution. The additives have been observed to affect the CMC of the surfactants and the Epirubicin-micelle binding constant appreciably. The presence of NaCl and glucose lowered the CMC of all the surfactants studied. The binding constant of Epirubicin decreased in the presence of NaCl but increased in the presence of glucose. The equilibrium complex formation constant between Epirubicin and SDS decreased in the presence of NaCl compared with purely aqueous media. (C) 2004 Wiley-Liss, Inc. and the American Pharmacists Association.
Keywords: interaction; surfactants; SDS; TX100; Tween 20; Epirubicin HCl; binding constant; NaCl; glucose; Job's method; PERFORMANCE LIQUID-CHROMATOGRAPHY; SODIUM DODECYL-SULFATE; IONIC MICELLES; ABSORPTION-SPECTROSCOPY; PROTOTROPIC EQUILIBRIUM; ELECTRONIC ABSORPTION; NONIONIC MICELLES; CACO-2 CELLS; FLUORESCENCE; BINDING